2019
DOI: 10.1111/ijd.14381
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata in Tunisia: epidemio‐clinical aspects and comorbid conditions. A prospective study of 204 cases

Abstract: Background Alopecia areata (AA) is an autoimmune condition that usually presents as patchy, nonscarring hair loss. Autoimmune disorders and atopy are reported as comorbid conditions. We aimed to investigate the demographics, clinical characteristics, and associations of AA in Tunisian patients. Methods Demographic data, pattern of alopecia, age of onset, and associations were evaluated in 204 patients from January 2012 to June 2016. Results Two hundred and four cases of AA were seen. The male to female ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
4
15
1
Order By: Relevance
“…Similarly, a study conducted in Egypt which included 60 patients stated that patchy alopecia was the commonest (53.3%), then both totalis and universalis with lesser frequencies (26.7%) [15]. Besides, a study in Tunisia performed on 204 patients showed similar findings to ours [16]. Therefore, patchy alopecia is the most commonly encountered pattern of hair loss in dermatology clinics as revealed by our study and other previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, a study conducted in Egypt which included 60 patients stated that patchy alopecia was the commonest (53.3%), then both totalis and universalis with lesser frequencies (26.7%) [15]. Besides, a study in Tunisia performed on 204 patients showed similar findings to ours [16]. Therefore, patchy alopecia is the most commonly encountered pattern of hair loss in dermatology clinics as revealed by our study and other previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…This is in contrast with other studies in the literature which demonstrated atopic disease as the most common comorbidity followed by hypothyroidism as the second most common. For example, Arousse et al found that atopic disease occurred in 18.1% of their sample whereas hypothyroidism was noted in 12.7% of cases [16]. However, a previous local study demonstrated findings similar to ours as hypothyroidism was the most common comorbidity in their sample [14].…”
Section: Figure 1: Zinc Levels In Relation To Alopecia Typessupporting
confidence: 58%
“…Apart from this, we believe that this observation might be a peculiarity of alopecia areata in Africa, given that certain pathologies may be clinically discovered. The clinical forms found were proportionally identical to those in the literature [3,4,6,7]. Treatment in our work context was based on locally applied topical remedies; these were mainly dermocorticoids and minoxidil solution, used in combination or not.…”
Section: Discussionsupporting
confidence: 71%
“…According to Salam et al, the most common etiology of nonscarring alopecia in African women is traction alopecia [5]. Several pathologies can be associated with alopecia areata, and these include thyroiditis, vitiligo, psoriasis, diabetes, lichen planus, atopic dermatitis, and numerous other diseases described in the literature [6][7][8][9]. However, our study found no pathologies associated with alopecia areata.…”
Section: Discussioncontrasting
confidence: 48%
“…There are also reports from vitiligo, alopecia areata, rheumatoid arthritis, pernicious anemia, systemic lupus erythematosus, Sjögren syndrome, and multiple sclerosis ( 110 , 111 , 113 116 ). In 5.7% of patients, morphea coexists with LS, especially the circumscribed and generalized types ( 117 ).…”
Section: Associationsmentioning
confidence: 99%